Tracking aquaculture-derived fluoroquinolones in a mangrove wetland, South China. (December 2016) - Liu, Xiao; Liu, Yu; Xu, Jian-Rong; Ren, Ke-Jun; Meng, Xiang-Zhou
Abstract: Aquaculture in mangrove wetlands has been developed rapidly, causing various environmental problems (e.g., antibiotic residue). In the present study, the levels and distributions of a well-known class of antibiotics (fluoroquinolones; FQs), including norfloxacin (NOR), ciprofloxacin (CIP), and enrofloxacin (ENR), were examined in sediment and mangrove plant ( Aegiceras corniculatum ) from a mangrove wetland in the Zhanjiang Mangrove National Nature Reserve, South China. NOR and CIP were detected in all sediment samples, with concentrations ranging from 4.3 to 64.2 ng/g and from 7.62 to 68.5 ng/g on a basis of dry weight (dw), respectively, whereas ENR was found with relatively lower frequency (<78%) and lower concentrations (<19.3 ng/g). Sediments in mangrove rhizosphere area contained considerably higher concentrations of all FQs (except for ENR). FQs were largely varied in mangrove plant tissues; NOR and ENR were not detected in leaf and root samples, respectively. CIP featured an increasing tendency from the root to the upper parts of plants, whereas a decreasing trend was found for NOR. Three bioconcentration factors (BCFs ) of FQs, including BCFs for roots (BCFr ), branches (BCFb ), and leaves (BCFl ) were calculated, and most of them exceeded 1. Especially for NOR, its BCFr can reach up to 9.9, indicating that Aegiceras corniculatum has a strong ability to accumulate FQs from sediment and/or surrounding environment. For NOR and CIP, strong positive relationships were observed between BCFr and concentrations in root, but no significant correlations were observed between BCFr and root lipid of mangrove plant. More studies are needed to investigate the uptake mechanism of antibiotics in mangrove plants. Graphical abstract: Highlights: FQs in sediment and plant from mangrove wetland were analyzed. NOR and CIP were detected in all sediment while ENR had the lowest level. FQs had correlation with TOC and pH, with higher level found at mangrove rhizosphere area. Most BCFs exceeded 1, indicating that Aegiceras corniculatum can accumulate FQs. Abstract : Aquaculture-derived fluoroquinolones can be captured in mangrove wetlands.